Power and agency in the lives of contemporary Tibetan nuns: an intersectional study - Härkönen, Mitra (The study of religion in a global context, 2023)
"This book examines the lived experiences of oppression and opportunities encountered by contemporary Tibetan Buddhist nuns living in the People's Republic of China and the Tibetan exile community in India. It investigates how the intersections of the nuns' female gender, their Buddhist religion and their Tibetan nationality on the one hand produce subordination and an unequal distribution of power but, on the other, provide the nuns with opportunities and agency"--